FORMATION OF COMPETENCY-BASED MODEL IN PROFESSIONAL TRAINING OF MODERN DOCTOR - M. G. Romantsov; I. Yu. Melnikova; A. A. Shuldyakov; O. V. Shamsheva (Детские инфекции (Москва), 2015)
The shift in priorities in the system of Russian education, transition from reproductive learning to learner-centered approach, incorporation of competency-based approach into the educational standards of «the third generation» require the training of a competitive specialist with professional competency. Types of competencies are characterized. The competency presenting certain requirements is studied. The mastering of the requirements will enable to train qualified specialists. The quality of education directly influences the level of professional activity through training of specialists and development of sciences. Competence-oriented approach and adherence to pedagogic requirements in education enables the efficacy of professional training. Innovative techniques and approaches to organizing educational process in their active form stimulate the process of studying.